2015
DOI: 10.1074/jbc.m115.669960
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Assembly of the Adeno-associated Virus Type 2 Rep68 Protein on the Integration Site AAVS1

Abstract: Background: Rep68 catalyzes site-specific integration into chromosome 19 AAVS1 site. Results: Rep68 forms a heptameric complex on the AAVS1 site. Conclusion: Assembly requires the cooperative interaction of all functional domains and requires a minimum of two GCTC repeats. Significance: These results provide insights into the first step of the site-specific integration reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Numerous groundbreaking studies, although not based on high-throughput sequencing, have demonstrated the preferred integration of wtAAV2 into AAVS1--located at human chromosome 19--and have uncovered the molecular mechanism underlying this integration preference, identifying the multifunctional, nonstructural wtAAV Rep proteins by AAV2's inverted terminal repeats and AAVS1 (Rep-binding sites and terminal resolution sequence motifs) as key factors. [5][6][7][8] Consistent with this, several pubvectors gained AAVS1 targeting upon administration of Rep protein. [9][10][11][12] As yet, only two large-scale wtAAV integration analyses performed on primary cells have been published.…”
Section: Reply To "Wild-type Aav Insertions In Hepatocellular Carcinomentioning
confidence: 68%
“…Numerous groundbreaking studies, although not based on high-throughput sequencing, have demonstrated the preferred integration of wtAAV2 into AAVS1--located at human chromosome 19--and have uncovered the molecular mechanism underlying this integration preference, identifying the multifunctional, nonstructural wtAAV Rep proteins by AAV2's inverted terminal repeats and AAVS1 (Rep-binding sites and terminal resolution sequence motifs) as key factors. [5][6][7][8] Consistent with this, several pubvectors gained AAVS1 targeting upon administration of Rep protein. [9][10][11][12] As yet, only two large-scale wtAAV integration analyses performed on primary cells have been published.…”
Section: Reply To "Wild-type Aav Insertions In Hepatocellular Carcinomentioning
confidence: 68%
“…The conserved N-terminal region of the MVC NS proteins encodes a histidine- hydrophobic-histidine (HUH) endonuclease motif (35,36), also conserved in other parvoviral nonstructural proteins (13,36), which is required for site-specific DNA cleavage and ligation during rolling-hairpin replication (12,37). The active site of the MVC HUH motif is predicted to be H122, L123, and H124, which are present in all the MVC NS isoforms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when a small fluorescent DNA molecule binds a protein, the larger complex will rotate more slowly than the DNA molecule, changing the plane of the polarized light and increasing the anisotropy value. We have used this technique to measure the binding affinity of AAV Rep68 for different DNA substrates (Yoon-Robarts et al , 2004; Musayev et al , 2015; Bardelli et al , 2016). The non-structural AAV Rep proteins carry out most of the DNA transactions that are required to complete the virus life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…These include DNA replication, transcriptional regulation, site-specific integration and packaging of DNA into preformed capsids (Im and Muzyczka, 1990; Weitzman et al , 1994; Wonderling et al , 1995). The large AAV Rep proteins (Rep78/Rep68) contain an N-terminal origin binding domain (OBD) that specifically binds the Rep binding sites (RBS) and displays nuclease activity (Hickman et al , 2004; Musayev et al , 2015). The RBS sites consist of two or more 5′-GCTC-3′ repeats and are found at the viral origin of replication, in several promoters and at the AAVS1 integration site (Weitzman et al , 1994; McCarty et al , 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation